Kepribadian Tokoh Hosie dalam Cerita Pendek Hana no Warutsu - Fajar Dwi Ariyadi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The short story of Hana no Warutsu by Kawataba Yasunari has the theme of a dancer's fear, love of dance, and body defects that make the dancer's dream disappear. This study aims to conduct a psychological analysis to reveal the state of Hosie's character. This research method uses qualitative descriptive techniques in analyzing the psychological condition of the Hosie with the approach of Medrad Boss's existential psychological theory. The research procedure used in this study is to determine the material object, disclose research data, and analyze Hosie's character in the short story of Hana no Warutsu. The results showed that Hosie was gifted with talent and a deep love for dance but denied it. He was afraid to get too caught up in the dance, so he tried to run away by stopping dancing. This escape makes his life inauthentic, and his existence shrinks. When he saw the dance, his existence pushed him to dance, causing him to be unable to control himself.